Monstrous Gender Performances in Macbeth - Van Laak, Felicitas (Satura, 2020)
In his essay “Monster Culture (Seven Theses),” Jeffrey J. Cohen defines and deconstructs textual monsters, his base assumption being that each monster helps understand the culture it is born into. Derived from the Latin monstrare, which means ‘to show,’ a monster indirectly points to the deeply rooted fears and anxieties of a society at a certain point in time. The monstrous is a shapeshifter, depending on constant reinterpretation. Consequently, I aim at deconstructing monstrous physicality to reveal the cultural anxieties it embodies. While Shakespeare inflationarily uses various forms of the term ‘monster’ when referring to Caliban in The Tempest, it appears only twice in Macbeth. Nevertheless, the performance history of Lady Macbeth and the witches a strong association with monstrosity. This essay follows the proposition that “the body in play bears continuous meaning onstage, and always exceeds the play text it inhabits” (Rutter xiii), as well as Butler’s premise that gender is a performance. I will use Cohen’s theory to illustrate the sexualising and othering strategies that support misogynist representations of Lady Macbeth and the witches. This article covers two 2018 productions of Macbeth starting with the live recording of the performance from the Royal Shakespeare Company (RSC) directed by Polly Findlay. Then, I will discuss Kit Monkman’s “radical new adaptation,” which claims to “amplify[ ] the theatrical context of the original whilst creating truly innovative and thrilling cinematic vistas.”